An unusual case of penetrating head injury following road traffic accident - Pandey, Mithilesh Kumar; Roy, Kaushik; Chaudhuri, Gaurab; Saha, Suniti Kumar (Asian Journal of Medical Sciences, 2015)
A 35 year old male was presented with discharging sinus at left frontozygomatic region with trismus for last 1 month. The patient had a past history of penetrating trauma in the vicinity of the left frontozygomatic area following road traffic accident 6 months back. 3D-CT skull was showed a linear dense radiolucent foreign body obliquely placed in the left temporal and infratemporal fossa. Trismus due to trauma usually follows road accidents leading to massive faciomaxillary injury. But in this case an initial minor penetrating injury was presented trismus in delayed fashion. The aero digestive tract is the commonest site involved in foreign body lodgement in head and neck region. However the lodgement of foreign-body in an area of infratemporal fossa with unusual symptoms of trismus is quite rare and only few cases have been reported in the literature so far following a road traffic accident. DOI: http://dx.doi.org/10.3126/ajms.v6i5.12329 Asian Journal of Medical Sciences Vol.6(5) 2015 75-77